The Impact of Course Brand and Content Marketing Expert for SME inIncreasing Student Entrepreneurship (Study on Alumni Students of the Indonesian Student Micro Credential Program, Makassar State University) - Rismayanti Rustam; Herlina Sakawati; Sitti Hardiyanti Arhas (Public Resource Innovation Management and Excellence, 2024)
This study aims to find out how the impact of the Course Brand and Content Marketing Expert for SMEs in Increasing Student Entrepreneurship (Study on Alumni Students of the Indonesian Student Micro Credential Program, Makassar State University) and to find out what factors hinder and support training. This study uses a qualitative research method with a case study type of research. Data collection techniques used were observation, interviews and documentation with 10 informants. Data analysis techniques in this study used data analysis techniques in the form of data condensation, data presentation and drawing conclusions. The results showed that the goals and objectives of this training in the form of creating novice entrepreneurs among students had been achieved but were still not optimal. However, this training had a positive impact on most of the participants in the form of adding new knowledge and skills in starting a business as well as in running and developing a business by utilizing various knowledge and skills acquired during the training, both in terms of planning, packaging to technology and internet-based marketing. The inhibiting factors for the training were that the training was carried out online, there were difficulties for participants in participating in the training, especially during packaging design practices, the short training only lasted for a month, the participants did not pay attention to the detailed attendance and class schedules so that it was necessary to control the level head, the tasks quite a lot with close deadlines, tight schedules in one week and the distance between one material and another close together. While several supporting factors in this training include the balance of the training material provided both in theory and practice, the instructor or teacher is someone who has competence in the business field, the presence of trainers or presenters who are entrepreneurs or practitioners, the knowledge and skills acquired are related to the modern era by utilizing technology and the internet as well as compensation for converting course grades, certificates and some pocket money.